Association of genomic variants at PAX8 and PBX2 with cervical cancer risk - Ramachandran, Dhanya; Wang, Yingying; Schuermann, Peter; Huelse, Fabienne; Mao, Qianqian; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; Hirchenhain, Christine; Schmidmayr, Monika; Mueller, Florian; Runnebaum, Ingo; et al. (International Journal of Cancer, 2021)
Cervical malignancy is triggered by human papillomavirus infection but the risk for cervical cancer has a hereditary component. From a recent Genome Wide Association Study meta-analysis, 2q14.1 (PAX8) and 6p21.32 (PBX2) have been proposed as novel cervical cancer susceptibility loci. We investigated the two main signals at these loci in an independent case-control series of 2578 cases with cervical dysplasia or carcinoma and 1483 healthy females. We find significant associations for both variants, rs10175462 at PAX8 and rs2856437 at PBX2, with overall cervical disease (rs10175462: odds ratio [OR] 0.82, 95% confidence interval [CI] 0.74-0.91, P = 2.4 × 10−4; rs2856437: OR 1.52, 95% CI 1.14-2.02, P =.004). Both variants showed evidence of association with invasive squamous cervical cancer (rs10175462: OR 0.80, 95% CI 0.68-0.94, P =.006; rs2856437: OR 1.56, 95% CI 1.03-2.36, P =.036) and with high-grade dysplasia (rs10175462: OR 0.79, 95%CI 0.70-0.90, P = 1.9 × 10−4; rs2856437: OR 1.58, 95% CI 1.15-2.17, P =.005). A combined analysis of high-grade dysplasia and invasive cervical cancer also showed significant associations for both variants (rs10175462: OR 0.81, 95% CI 0.73-0.91, P = 2.4 × 10−4; rs2856437: OR 1.57, 95% CI 1.18-2.10, P =.002). No association was detected for rs2856437 with low-grade dysplasia, while rs10175462 showed weak evidence of association (P =.05). RNA analyses in cervical samples revealed that PAX8 transcripts were upregulated in HPV-positive lesions (P =.008) but this was not observed in the presence of the protective minor allele of rs10175462. The rs10175462 genotype also correlated with reduced levels of the lncRNA PAX8-AS1 (P <.001). Taken together, our results extend the evidence for a link between genomic risk variants at the HLA region (PBX2) with cervical disease and support PAX8 as the first consistent non-HLA cervical cancer susceptibility locus.
CRIS-Team Scopus Importer:2021-05-21
Keywords: association study; cervical malignancy; eQTL; HPV infection; single nucleotide polymorphism